What is the Influence of the Global Economic Crisis on the Development of the Wage Distribution of Czechs and Slovaks? - Bílková, Diana (Asian Journal of Economic Modelling, 2014)
This paper deals with the development of wage distribution by gender in the Czech and Slovak Republics in the years 2005–2012. Special attention is given to the changing in the behavior of the wage distribution in relation to the onset of the global economic recession. The different behavior of the wage distribution of Czech and Slovak employees during the period is the subject of research. The article discusses the differences in wage level between men and women in the Czech and Slovak Republics. There are the total wage distributions of men and women together, both in the Czech Republic and in the Slovak Republic on the one hand, and wage distributions according to the gender separately for men and for women on the other hand. Comparison of wage levels in the world and the position of wages of the Czech employees in the international context is included, too.